Simultaneous Detection of Key Bacterial Pathogens Related to Pneumonia and Meningitis Using Multiplex PCR Coupled With Mass Spectrometry - Zhang, Chi; Xiu, Leshan; Xiao, Yan; Xie, Zhengde; Ren, Lili; Peng, Junping (Frontiers in Cellular and Infection Microbiology, 2018)
Pneumonia and meningitis continue to be an enormous public health burden and pose a major threat to young children. Among all the causative organisms, bacterial pathogens are the leading cause of serious cases and deaths. It is challenging to identify the correct infectious agent accurately and rapidly. To solve this problem, we developed and validated a 12-plex method (BP-MS), which can simultaneously screen 11 key bacterial pathogens related to pneumonia and meningitis. The BP-MS method is based on the multiplexed PCR coupled with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) platform. Forty-six confirmed nasopharyngeal swabs and twelve isolates were used to validate the specificity. The results showed that the BP-MS method could accurately identify expected bacteria without cross-reactivity with non-target pathogens. For all the 11 target bacterial pathogens, the analytical sensitivity of the BP-MS method can be down to a concentration of 10 copies/reaction. To further evaluate the clinical effectiveness, 204 nasopharyngeal swabs from hospitalized children with suspected pneumonia syndrome were tested by the BP-MS method. 81.9% (167/204) of the samples were positive for at least one of the 11 target pathogens. Among all the 167 positive samples, multiple infection rate was 55.7% (93/167) and the most frequent combination was Streptococcus pneumoniae with Haemophilus influenzae, for 46.2% (43/93) mixed infections involved the two pathogens. Then we used real-time PCR and nested PCR to further confirm the positive results. Identical results were obtained in 81.4% (136/167) of the positive samples. The BP-MS method is a sensitive and specific molecular detection technique with high multiplex and throughput. Therefore, it will be a powerful tool for pathogen screening and antibiotics decision-making at the early stage of disease.